INTERNALIZING STUDENTS' MORAL VALUES THROUGH ISMUBA LEARNING IN THE MODERNIZATION ERA - Roihan Arrosyid (Indonesian Journal of Islamic Studies (IJIS), 2026)
This study focuses on the internalization of moral values among students in facing the challenges of modernization, such as moral degradation and youth relations. This study uses qualitative methods. The data analysis techniques in this study are data presentation, data discussion, and conclusion drawing. The results of this study identify four key aspects, namely: 1) Pre-learning planning for students is very important to determine the aspects of learning that will be implemented in the classroom, 2) The implementation of ISMUBA learning based on moral knowing and feeling will focus more on students' moral education, 3) Teachers' exemplary behavior as role models for students because good activities must be exemplified first, and 4) Learning projects/training students' skills through learning outside the classroom trains students to face daily challenges and fosters moral action. The main challenges in moral internalization include a lack of teacher role models, a lack of supervision of outside classroom activities, and external factors due to the influence of social media. Therefore, this study recommends cooperation among educators, namely schools, teachers, and families, to strengthen the effective moral internalization of students.